Flaubert, lire le journal - Jérémy Naïm (Flaubert: Revue Critique et Génétique)
How is the reading of the diary represented in Flaubert? This article hypothesises a unified representation of what will be called a "media regime of reading" in the Correspondence and in the work. To read in a media regime would be, by nature, to read by diverting and turning away, forgetting the text in favour of oneself. The characterisation of this regime would make it possible to better understand Flaubert's hatred of the newspaper and to nuance somewhat the portrait of the writer as a hermit who would refuse any compromise with the press.